La reduplicación léxica en español: origen, presencia, interpretación - Stala, Ewa (Studia Romanica Posnaniensia, 2019)
On this occasion we will try to approach a topic that is not mentioned in the grammars, despite being quite frequent in the Spanish language, especially in its colloquial variety: that of the lexical reduplication type café café or guapo guapo. We begin with the explanation and presentation of the phenomenon and then focus only on the lexical reduplication i.e. the repetition of whole lexemes. We will present its mechanism of quantification (Roca and Suñer 1998), the supposed origin (Paasch-Kaiser 2015), its presence in the corpus and the theories about the role it plays in the language (Escandell Vidal 1991). In the end, we will proceed with the explanation of this phenomenon in terms of pragmatics, above all, that of illocutionary semantics (Wierzbicka 1999) and linguistic ethos (Baran 2010a, 2010b; Kerbrat-Orecchioni 2005; Nowikow 2003, 2006).